(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
This article describes the difficult and persecuted life of Maryam Sultanmuradova, one of the talented Turkestan students who studied in Germany in the 20s of the 20th century, her contribution to the field of science, and the bitter memories narrated by her daughter Anor Davronova.